Direct shear test and model prediction analysis of unsaturated silt. Issue 1 (June 2020) - Zhou, Huiwen; Zhao, Peng; Du, Xueming
Abstract: In order to study the mechanical properties of Unsaturated Silt in the east of Henan Province, the influence of water content, normal stress, degree of compaction and dry density is studied through direct shear test and model prediction. The results of direct shear test show that with the increase of moisture content and normal stress, the shear deformation of soil gradually changes from softening to hardening, and the higher the dry density is, the more obvious the phenomenon is. In addition, the cohesion decreases with the increase of water content, and the curve is broken line, and the turning point appears near the optimal water content; the influence of water content on the internal friction angle is small, and the internal friction angle increases with the increase of dry density at the same water content. At the same time, the hyperbolic model can well predict the direct shear test results, especially in the case of high normal stress, low density and high moisture content, the more the model prediction value is close to the test value.